2017
DOI: 10.4314/ijbcs.v10i4.6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of schistosomiasis and intestinal helminths following mass drug administration in the Centre and Plateau Central regions of Burkina Faso

Abstract: Schistosomiasis is the most important waterborne disease in Sub-Saharan Africa. Transmission is governed by the spatial distribution of specific freshwater snails that act as intermediate hosts and human water contact patterns. In developing countries, such as Burkina Faso it remains a serious health problem, which management face important gaps. The main of theses gaps is the lack of reliable information about prevalence. Then, this study has been undertaken in order to determine the prevalence of schistosomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…La comparaison entre les trois sites d'étude a montré que la prévalence de l'infection à S. haematobium dans le village de M'Pèba (72,36%) était nettement supérieure à celles des villages de Guénidanga (52,61%) et de Kalabougou (24,4%) ; P< 10 -6 (Tableau 4). Ces taux de prévalence de S. haematobium sont nettement supérieurs à ceux obtenus par Zongo et al (2016) dans deux régions du Burkina Faso soient 4% et 0,6% avec une moyenne de 2,3% (95% CI: 1,5% -3,1%). Pour tous les villages confondus, la prévalence de l'infection à S. haematobium entre sujets de sexe différent n'était pas significativement différente.…”
Section: Données éChographiquesunclassified
“…La comparaison entre les trois sites d'étude a montré que la prévalence de l'infection à S. haematobium dans le village de M'Pèba (72,36%) était nettement supérieure à celles des villages de Guénidanga (52,61%) et de Kalabougou (24,4%) ; P< 10 -6 (Tableau 4). Ces taux de prévalence de S. haematobium sont nettement supérieurs à ceux obtenus par Zongo et al (2016) dans deux régions du Burkina Faso soient 4% et 0,6% avec une moyenne de 2,3% (95% CI: 1,5% -3,1%). Pour tous les villages confondus, la prévalence de l'infection à S. haematobium entre sujets de sexe différent n'était pas significativement différente.…”
Section: Données éChographiquesunclassified
“…Whereas the current study adopted a prospective design, that was conducted in Nairobi adopted a ten-year retrospective design which is often fraught with incomplete data that may cause proportionate variations on the factors of interest. Squamous cell carcinoma proportion in this study could be attributed to chronic urinary tract infections from either bacteria or Schistosoma haematobium parasite which are prevalent in Western Kenya which is within the Lake Victoria basin 10,37 . This study reported that nine in ten (91.1%) of the participants had low grade tumors with 8.9% presenting with high grade tumors.…”
Section: Discussionmentioning
confidence: 73%
“…About 50 million cattle and 70 million sheep and goats are at risk for AAT and an estimated three million cattle die from the disease annually in Africa (Simarro et al, 2010). As the parasite maneuvers ways to avoid the animal's immune system, and in the absence of a suitable vaccine, surveillance, speedy diagnosis and treatment with existing drugs are not effective and vector control efforts will go a long way in decreasing the incidence of AAT (Oyibo et al, 2009;Zongo et al, 2016). AAT still remains by far the most devastating parasitic and neglected zoonotic disease in Africa, affecting both humans and livestock.…”
Section: Prevalence Of Trypanosomiasis In Cattle In the Gambiamentioning
confidence: 99%